Study of the Crystal Chemistry of the n = 2 Ruddlesden−Popper Phases Sr3FeMO6+δ (M = Fe, Co, and Ni) Using in Situ High Temperature Neutron Powder Diffraction - Mogni, Liliana Verónica (2009)
Effects of the substitution of Fe by Co or Ni on the crystal structure of the n = 2 Ruddlesden-Popper phase Sr3Fe2O 6+ δ have been studied by in situ high temperature neutron powder diffraction (NPD) in the temperature range 20 °C ≤ T ≤ 900°C. The analysis of neutron diffraction data confirmed that for a given temperature the oxygen non-stoichiometry increases when Fe is replaced by Co or Ni. Oxygen vacancies were detected at the crystal sites O(1), connecting the octahedra along the oaxis, and O(3) in the FeO2 planes of the perovskite layers. The substitution of Fe by Co or Ni increases the oxygen vacancy concentration at the O(3) crystal site, which were detected even when the total oxygen content was higher than 6.00. This result supports a diffusion mechanism involving the migration of oxide ions from the O(3) site to its adjacent empty O(1) sites and vice versa. The average linear expansion αave≈ 1/3 αvol calculated from NPD data increases with the substitution of Fe by Co or Ni (19.9,25.1, and 22.7 × 10-6K-1for M = Fe, Co and Ni, respectively). The expansion along the c-axis(αc) affects mainly the perovskite block while the width of the rock-salt block remains constant. The crystal structure expansion is discussed considering the thermal and chemical contributions, along with the effect of the increasing delocalization of charge carriers when Fe is renlaced with Co or Ni.